The Depression Prevention Initiative: Mediators of Interpersonal Psychotherapy–Adolescent Skills Training. Issue 2 (4th March 2021) - Jones, Jason D.; Gallop, Robert; Gillham, Jane E.; Mufson, Laura; Farley, Alyssa M.; Kanine, Rebecca; Young, Jami F.
Abstract : Several adolescent depression prevention programs have demonstrated effects on depressive symptoms and overall functioning. Yet, despite an increasing emphasis on elucidating mechanisms of change in interventions, few studies have identified mediators of these preventive interventions. In this study, we examined interpersonal mediators of Interpersonal Psychotherapy–Adolescent Skills Training (IPT-AST), an evidence-based depression prevention program. The Depression Prevention Initiative is a school-based randomized controlled trial in which 186 adolescents ( M age = 14.01, SD  = 1.22; 66.7% female; 32.2% racial minority) were assigned to receive either IPT-AST ( n = 95) or Group Counseling (GC) ( n = 91). We examined whether change in interpersonal conflict, social support, or social functioning from baseline to midintervention mediated the effects of IPT-AST on depressive symptoms and overall functioning at postintervention. At postintervention, youth in IPT-AST had lower depressive symptoms ( d = −.31) and higher overall functioning scores ( d = .32) than youth in GC. Improvements in adolescent romantic functioning, reductions in peer conflict, and improvements in a factor score reflecting mother–adolescent conflict and difficulties in family functioning emerged as significant mediators. However, the effects of the intervention on change in the mediators were not statistically significant. These findings add to the sparse literature on mediators of psychosocial interventions, provide partial support for the theoretical mechanisms underlying change in IPT-AST, and highlight important directions for future prevention and intervention research.